PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENURUNAN PROKRASTINASI AKADEMIK - Emmanuella, Egidia (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2024)
Academic procrastination is one of the problems that students often experience in the learning process. This phenomenon refers to the tendency to procrastinate or avoid academic tasks that must be completed. In an effort to overcome the problem of academic procrastination, one intervention that can be carried out is through group guidance services. The group guidance process allows students to share experiences, provide support and learn strategies to overcome academic procrastination. This approach uses a type of quantitative research with a survey method, namely collecting data using a list of statements and giving it to respondents to answer. Apart from that, researchers also used interview and observation methods, by interviewing students who experienced a decrease in academic procrastination and directly observing the students' behavior. Then the researchers looked at the overall results of questionnaires, interviews and observations, then the researchers were able to find conclusions regarding the factors that influence the reduction in academic procrastination.